Un modelo integrado para el fortalecimiento de la gestión pública (Sistema de Gestión de Calidad - Balance Scorecard) (2009)
The articulation of the Quality Management System with the balance scorecard in Colombian´s public sector organizations is aiming to establish and standarize an integrated Management system which allows the measurement and evaluation of the the institucional strategy in relation with the vision and planning process, in terms of efficay, efficiency and efectiveness to assure the fullfillment of the social object and to gain social and economic benefit for all the country